Long-term trends of pH and inorganic carbon in the Eastern North Atlantic: the ESTOC site - González-Dávila, Melchor; Santana-Casiano, J. Magdalena (Frontiers in Marine Science, 2023)
Using 25 years of data from the North-East Atlantic Ocean at the ESTOC site, we confirm the surface ocean is actively absorbing carbon emissions caused by human activities and undergoing ocean acidification. The carbon dioxide is also increasing in the subsurface and deepest waters. Seawater salinity normalized inorganic carbon (NCT), fugacity of CO2 (fCO2) and anthropogenic CO2 increase at a rate of 1.17 ± 0.07 µmol kg−1, 2.1 ± 0.1 µatm yr−1 and 1.06 ± 0.11 μmol kg−1 yr−1, respectively, while the ocean pHT fixed to the average temperature of 21°C, declines at a rate of 0.002 ± 0.0001 pH yr−1 in the first 100 m. These rates are 20% higher than values determined for the period 1995–2010. Over the 25 years, the average surface fCO2 increased by 52.5 µatm while the pHT declined by 0.051 pH units ( 13% increase in acidity), like the observed seasonal signal. After 2020, seawater conditions are outside the range of surface fCO2 and pHT seasonal amplitude observed in the 1990s. It was also predicted by the year 2040, fCO2 seawater data will be smaller than atmospheric one and the area will be acting as a sink the full year around. Parameterizations of AT, CT, pHT and fCO2 using observations of water temperature, salinity and dissolved oxygen were determined for the ESTOC site with standard error of estimation of 6.5 µmol kg−1, 6.8 µmol kg−1, 0.010 pH and 9.6 µatm, respectively, and were applied to the North-East Atlantic Ocean. The observations and the parameterizations showed that the trends of the carbonate variables along the water column in the eastern subtropical ESTOC region are dominated by anthropogenically induced changes, observed in the whole water profile.